Revising primary and secondary school curricula in the Caribbean to enhance education on the risks for noncommunicable diseases - Waneisha Jones; Natasha Sobers; Alsian Brown-Perry; Laurette Bristol; T. Alafia Samuels (Pan American Health Organization, 2023)
In the English-speaking Caribbean, an estimated 46% of men and 61% of women are currently overweight or obese, and 8% of children younger than 5 years are also overweight. To combat this worsening epidemic, driven by unhealthy dietary patterns, the Heads of Government of the Caribbean Community (CARICOM) issued the 2007 Port-of-Spain Declaration, which included mandates on the provision of healthy school meals, promotion of healthy dietary patterns, and reintroduction of physical education in schools. These mandates are aligned with evidence-based approaches used in childhood obesity prevention programs. School-based interventions, including curriculum revisions, are part of a multipronged approach to improve nutrition in children and are designed to complement and reinforce other interventions in schools. However, formal evaluation of the Port-of-Spain Declaration showed that most CARICOM member countries had difficulty implementing the mandates related to schools and diet. The Improving Household Nutrition Security and Public Health in the CARICOM project, in collaboration with regional institutions, the CARICOM Secretariat, and the Caribbean Examinations Council, sought to enhance nutrition education through revision of region-wide primary and secondary school curricula to increase the focus on prevention of noncommunicable diseases. This paper describes the process of revising the Caribbean Examinations Council's Human and Social Biology syllabus for secondary schools and the CARICOM Health and Family Life Education Regional Curriculum Framework for primary schools, which was achieved through multisectoral collaboration. We used the Framework for Reporting Adaptations and Modifications-Enhanced model to describe the process through which the modifications were made.